Plant water uptake modelling: added value of cross‐disciplinary approaches. (9th November 2022) - Dubbert, M.; Couvreur, V.; Kübert, A.; Werner, C.
ABSTRACT: In recent years, research interest in plant water uptake strategies has rapidly increased in many disciplines, such as hydrology, plant ecology and ecophysiology. Quantitative modelling approaches to estimate plant water uptake and spatiotemporal dynamics have significantly advanced through different disciplines across scales. Despite this progress, major limitations, for example, predicting plant water uptake under drought or drought impact at large scales, remain. These are less attributed to limitations in process understanding, but rather to a lack of implementation of cross‐disciplinary insights into plant water uptake model structure. The main goal of this review is to highlight how the four dominant model approaches, that is, Feddes approach, hydrodynamic approach, optimality and statistical approaches, can be and have been used to create interdisciplinary hybrid models enabling a holistic system understanding that, among other things, embeds plant water uptake plasticity into a broader conceptual view of soil–plant feedbacks of water, nutrient and carbon cycling, or reflects observed drought responses of plant–soil feedbacks and their dynamics under, that is, drought. Specifically, we provide examples of how integration of Bayesian and hydrodynamic approaches might overcome challenges in interpreting plant water uptake related to different travel and residence times of different plant water sources or trade‐offs between root system optimization to forage for water and nutrients during different seasons and phenological stages. Abstract : Here, we highlight how the creation of interdisciplinary hybrid plant water uptake models can embed plasticity of plant water uptake into a broader conceptual view of soil–plant feedbacks of water, nutrient and carbon cycling.